2012
DOI: 10.1111/j.1399-6576.2012.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

The perioperative combination of methadone and ketamine reduces post‐operative opioid usage compared with methadone alone

Abstract: Perioperative ketamine-ME combination significantly decreased opioid consumption by PCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 18 publications
1
35
0
3
Order By: Relevance
“…In the past several years it has been rediscovered as an important component of managing intraoperative and postoperative pain in patients undergoing complex spine surgery [52,53]. In addition to being an opioid agonist, methadone is also an NMDA antagonist, augmenting its ability to manage acute and chronic pain.…”
Section: Methadonementioning
confidence: 99%
“…In the past several years it has been rediscovered as an important component of managing intraoperative and postoperative pain in patients undergoing complex spine surgery [52,53]. In addition to being an opioid agonist, methadone is also an NMDA antagonist, augmenting its ability to manage acute and chronic pain.…”
Section: Methadonementioning
confidence: 99%
“…The 29 RTCs that tested therapies administered during the intraoperative period included systemic pharmacological therapies (19 studies) [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] and locoregional anesthetic drugs (10 studies) [67][68][69][70][71][72][73][74][75][76] (see Table 3).…”
Section: Intraoperative Therapiesmentioning
confidence: 99%
“…[64][65][66] Of the 5 RCTs that tested dexmedetomidine, [48][49][50][51][52] in 2 the use of dexmetomedine did not guarantee lower postoperative pain scores but was able to reduce opioid consumption when compared to placebo or midazolam; in 2 other studies it did not reduce postoperative pain when compared to the control group, and in 1 it was more effective than remifentanil in reducing postoperative pain and patient-controlled analgesia (PCA) consumption. Of the 5 RCTs that tested ketamine, [53][54][55][56][57] 4 studies proved that this drug can reduce opioid consumption but not pain scores when compared to placebo, while 1 study 54 found that low-dose ketamine was associated with lower pain scores but higher opioid consumption when compared to fentanyl. The 2 RCTs that tested tramadol found that it did not reduce pain scores but it was more effective than placebo and less effective than fentanyl in reducing opioid consumption.…”
Section: Intraoperative Therapiesmentioning
confidence: 99%
“…Studies have shown low-dose intravenous (IV) ketamine infusions to be a helpful adjunct in the treatment of postoperative pain especially in patients with chronic preoperative pain. 1,2,[6][7][8][9][10][11] Similarly, the drug has been shown to decrease discomfort in several chronic pain syndromes and conditions, such as complex regional pain syndrome, central neuropathic pain, peripheral neuropathic pain, postherpetic neuralgia, fibromyalgia, and cancerrelated pain. 12 Perioperatively, ketamine is primarily given intravenously; however, it is also effective via intramuscular, oral, and rectal routes.…”
mentioning
confidence: 99%